PENGARUH PERKEMBANGAN JUMLAH PELANGGAN kartuHALO MELALUI PROGRAM HALOfit TERHADAP TINGKAT PEMAKAIAN PULSA RATA-RATA PELANGGAN kartuHALO (STUDI KASUS DI TELKOMSEL GraPARI MAKASSAR) - Arfiany Arfiany (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The purpose of this research is to know the development of the number of kartuHALO Telkomsel subscribers through HALOfit program to the average user rate (ARPU: Average Revenue Per User) usage of kartuHALO Telkomsel Makassar area and how strong is the influence of the development of the number of kartuHALO Telkomsel customers through the HALOfit program on the level Usage of average customer pulse (ARPU) kartuHALO Telkomsel Makassar region. The research method used is a two-variable correlation analysis that is the development variable of the number of kartuHALO Telkomsel customers of Makassar region and the variable rate of average customer credit usage (ARPU) kartuHALO Telkomsel Makassar. Further analysis of both variables will use simple regression analysis. The results of this study is the result of correlation analysis between the development of the number of customers kartuHALO Telkomsel with the average customer pulse rate obtained correlation coefficient number -0.418 which means there is influence that is not unidirectional and is at the level of a relationship that is. Then the increase in the number of subscribers will result in a decrease in the average credit card usage rate of kartuHALO Telkomsel customers. The determinant coefficient obtained is 0.174, which means that every 100% increase of CardHALO subscribers, the average customer's average usage rate will decrease by 17.4%. The result of regression analysis on the development of the number of subscribers and the rate of average credit usage of kartuHALO Telkomsel customers is that there is a linear regression equation with negative direction which is Y '= 457,714 - 2,083X. The authors see this as a consequence of Telkomsel's policy of conducting market development strategies on kartuHALO's products by applying tariff diversification through the HALOfit program which enables middle-income customers to enjoy kartuHALO services.